Effect of Lycium barbarum Polysaccharides on the expression of endothelin-1 and its receptors in an ocular hypertension model of rat glaucoma - Mi, Xue-Song; Chiu, Kin; Van, Geoffrey; Leung, Justin Wai Chung; Lo, Amy Cheuk Yin; Chung, Sookja Kim; Chang, Raymond Chuen-Chung; So, Kwok-Fai (Neural regeneration research, 2012)
Lycium barbarum, a traditional Chinese anti-aging herb, has been shown to protect retinal ganglion cells （RGCs） in a rat chronic ocular hypertension （COH） model. Here, we investigated the expression of endothelin-1 （ET-1）, a strong vasoconstrictor, and its receptors, ETA and ETB, in the COH model and assessed the effects of Lycium barbarum on the ET-1 axis. Elevated intraocular pressure （IOP） was induced in the right eye of SD rats using argon laser photocoagulation. （1） The expression of ET-1, ETA and ETB in normal and COH retinas was studied. （2） Some COH rats were fed daily with Lycium barbarum Polysaccharides （LBP） using 1 mg/kg or phosphate-buffered saline （PBS） for 3 weeks （started 1 week before photocoagulation）. The effects of LBP on the expression of ET-1 and its receptors, ETA and ETB, in COH retina were evaluated. A semi-quantitative analysis of staining intensity was used to evaluate the expression levels of ET-1, ETA and ETB in retinal vasculature. We found that （1） Under COH condition, the immunoreactivity of ET-1 was increased in retina associated with an increase of ETB receptor immunoreactivity and a decrease of ETA receptor immunoreactivity. （2） After feeding COH rats with LBP, the expression of ET-1 was decreased with an increase of ETA expression and a decrease of ETB expression in the retina, especially in RGCs. （3） By comparing the staining intensity in the vasculature of COH retina in LBP-fed group with PBS-fed group, there was a decrease in the expression of ET-1 and ETA and an increase in ETB. In summary, ET-1 expression was up-regulated in the retina in COH model. LBP could decrease the expression of ET-1 and modulate the expression of its receptors, ETA and ETB, under the condition of COH. The neuroprotective effect of LBP on RGCs might be related to its ability to regulate the ET-1-mediated biological effects on RGCs and retinal vasculature.